Analysis of the Level of Knowledge of Adolescent Reproductive Health in Preventing Sexual Deviations in High School Students - Hasibuan, Hotmaidah (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the level of knowledge of adolescent reproductive health and its relationship with the prevention of sexual deviance in students. Given the high risk of sexual deviance among adolescents, a comprehensive understanding of reproductive health is expected to equip them with the necessary knowledge to make responsible decisions and protect themselves from risky behavior. This study used a descriptive quantitative method with a survey approach. The research sample consisted of high school students in Arse. Sampling was done by cluster random sampling technique. The research instrument used was a questionnaire that had been tested for validity and reliability, including questions about basic knowledge ofreproductive health and understanding of various forms of sexual deviance. Data analysis was done descriptively to determine the level of knowledge of students and using a correlation test to see the relationship between the level of reproductive health knowledge and the potential prevention of sexual deviance. The results showed that the level of reproductive health knowledge of adolescents was still in the moderate category. Furthermore, correlation analysis showed a significant relationship between the level of reproductive health knowledge with understanding and attitude towards the prevention of sexual deviance. The implication of this study is the need to increase comprehensive and effective reproductive health education programs in the school environment to equip adolescents with sufficient knowledge in preventing sexual deviance.